Cognitive test as a tool for physics learning; WCPE 2012. The World Conference on Physics Education, Istanbul, Turkey, july 1-6, 2012 - Rogozin K.; Kuznetsov S. I. Sergey Ivanovich; Kondrashova D.; Lisina I. (2012, 2012)
В фонде НТБ ТПУ отсутствует